UJI DAYA TERIMA ROSELLA SEBAGAI BAHAN PEWARNA ALAMI DALAM PEMBUATAN SAUS CABE - Dina Sartika Nasution; Albiner Siagian; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Nowdays, consumption ofchilli saucein societycontinues to increase. However,there are manymanufacturers thatproduce chili saucenot under the good standard,so it candamage the healthof consumers. This happensbecause themanufacturers are tryingto meetthe market demandwantingchilisauceat a low price, so thatnot a fewmanufacturers whoignorestandards andfood safetyby adding. One of thehazard materialsaresynthetic dyesinchillisauceprocessing. Henceit is necessary toseek alternativenaturaldyesarerelativelysafe. Onenatural reddyethat can beused isRosella. bright red colorofthepetalsRosellaallure. However, the efficacy andthe benefits thatthe target of theconsumer. The type of this research is experiment. The objective of this research is to know the acceptable of chilli saucewith the addition of freshrosellaand chilli saucewith the additiondriedrosella. The variation of the addition are 10%, 20% and 30%. Acceptability test chilli saucerosellais conducted by using hedonic test to 30 panelists. Data wereanalyzed by using barlett test and analysis of variance test. These results showed that the addition 10% fresh rosella results in the most favorite taste by the panelist. While thechilisaucewiththe addition 10% dried rosella is the most favorite with color categoriy. The addition of rosella with many varieties influence the taste and color of chili sauce significantly. There is no influencing of the addition of rosella on the flavor and texture of chili sauce It is suggestedthatpeople use the rosella as analternative materialnatural dyein the manufacturesauces. Besidesthe addition ofrosellaas anatural dyein the manufacturechilisaucecan also createa different tastethatfresh acid tasteinchilisauce. Keywords: rosella flower, chili sauce, natural dye